Green Economy and Development (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
A green economy is an economy that aims at reducing environmental risks and ecological scarcities, and that aims for sustainable development without degrading the environment. It is closely related with ecological economics, but has a more politically applied focus.